Dendrimers: novel carriers for drug delivery - Chaudhari, H. S.; Popat, R. R.; Adhao, V. S.; Shrikhande, V. N. (Creative Pharma Assent, 2016)
Dendrimers are highly branched, organic compounds with well-defined, symmetrical structure. From chemical point of view they are three-dimensional polymers, characterized by a globular shape. At the end of the arms are terminals, functional groups, which can be easily modified in order to change their chemical and physical properties. Dendrimers have nanoscopic particle size range from 1 to 100 nm. They are ideal drug delivery systems due to their feasible topology, functionality and dimensions, their size is very close to various important biological polymers and assemblies such as DNA and proteins. The structure of dendrimer molecules begins with a central atom or group of atoms labeled as the “core.” From this central structure, branches of other atoms called ‘dendrons.’ The continuous branching results in layers of branch structure called “generations.”Synthesis of dendrimers done by four methods. These are ‘Divergent’ Dendrimer Growth , ‘Convergent’ Dendrimer Growth ,‘Double Exponential’ and ‘Mixed’ Growth ,‘Click’ Synthesis (Hypercores and branched monomers growth). Mechanisms of drug loading onto dendrimer carriers by physical encapsulation of drug molecules and chemical conjugation of drug molecules. The conjugates show increased solubility, decreased systemic toxicity and selective accumulation in solid tumors. Various applications as pharmaceutical and non pharmaceuticals. Dendrimers may have toxicity mainly attributed to the interaction of the cationic dendrimers surface with negative biological load membranes damaging cellular membranes causing hemolytic toxicity and cytotoxicity also limitation that does not apply where the drug is solubilised with dendrimer and then released in the gut for absorption. Some Marketed products of dendrimers are available named as Starburst, Priostar, Stratus CS, Vivagel, Alert ticket, SuperFect, Taxotere.